2018
DOI: 10.1080/15021149.2018.1507087
|View full text |Cite
|
Sign up to set email alerts
|

Piloting a brief relational operant training program: analyses of response latencies and intelligence test performance

Abstract: Previous research suggests that training relational operant responding using the SMART (Strengthening Mental Abilities with Relational Training) program over several months can result in improved performance on cognitive intelligence tests. This study aimed to investigate whether engaging in a 3-week relational training program would improve (i) scores and (ii) reaction times on a standardised intelligence test, and (iii) to pilot a new multiple exemplar training procedure targeting complex analogical operant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…We did not have an inactive control group to help to answer this question in the current study. One recent pilot study by McLoughlin et al (2018) found that a small dosage of SMART training helped to improve the speed at which participants completed the KBIT-2, while there was no such improvement in the inactive control participants. For this reason, it is arguably more probable that both SMART and Scratch were effective interventions for increasing processing speed.…”
Section: Discussionmentioning
confidence: 99%
“…We did not have an inactive control group to help to answer this question in the current study. One recent pilot study by McLoughlin et al (2018) found that a small dosage of SMART training helped to improve the speed at which participants completed the KBIT-2, while there was no such improvement in the inactive control participants. For this reason, it is arguably more probable that both SMART and Scratch were effective interventions for increasing processing speed.…”
Section: Discussionmentioning
confidence: 99%
“…If the hypothesis in the notation above were to be rejected in an experiment (i.e., if participants derived functions of a category that don't generally apply to it), the errors may be indicative of a deficit in hierarchical AARR abilities, and so training these generalizable patterns of behavior could be justified. Indeed, there are precedents in the literature for training both simple AARR (e.g., Cassidy et al, 2011) and more complex AARR repertoires (e.g., McLoughlin, Tyndall, & Pereira, 2018; see also Guinther, 2018).…”
Section: Crelmentioning
confidence: 99%
“…"Strengthening Mental Abilities with Relational Training" (SMART) is a commercial online program that trains relational framing operants (i.e., same/different and more/less relations) via multiple exemplar training in a gamified format. To date, several studies have suggested that training relational framing in this format leads to rises in IQ (Amd & Roche, 2018;Cassidy, Roche, Colbert, Stewart, & Grey, 2016;Cassidy, Roche, & Hayes, 2011;Colbert, Tyndall, Roche, & Cassidy, 2018;McLoughlin, Tyndall, & Pereira, 2018;Parra & Ruiz, 2016;Thirus, Starbrink, & Jansson, 2016;Vizcaíno-Torres et al, 2015) and there are putative indications of improvements in educational outcomes (Cassidy et al, 2016;J. Hayes & Stewart, 2016).…”
mentioning
confidence: 99%